A Half‐Century Odyssey in the Realm of Reactive Intermediates. Issue 1 (18th February 2015) - Moss, Robert A.
Abstract: Through a retrospective examination of the author's half‐century immersion in physical organic chemistry, an attempt is made to identify some broader currents in the field. Among these are the cyclical nature of physical organic chemistry, the persistence of research themes, the driving force of new instrumentation, paradigm shifts in theory, greater computational power, enhanced time resolution of experiments, and the export of mechanism‐based analysis to other foci of contemporary science. Abstract :